Unresolved chronic ulcerated nodules: Disseminated Cutaneous Sporotrichosis (Bangladesh Journal of Medical Science, 2022)
We present a case of disseminated cutaneous sporotrichosis in a 72-year-old male patient who has multiple ulcerated painless nodules over the left side of his chest and on his upper and lower left limbs for three years. He was initially diagnosed to have nodular vasculitis based on early repeated biopsies. Despite the patient’s good compliance with his prednisolone medication, no significant clinical improvement was observed. Another biopsy, which was arranged after two years of treatment for nodular vasculitis, supported the diagnosis of sporotrichosis. Itraconazole was initiated, and all the lesions showed a remarkable response toward the treatment. The delay in finding the correct diagnosis unnecessarily exposed the patient to the side effects of steroid and caused the disease to worsen.Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 191-195